Protocol for a process-oriented qualitative evaluation of the Waltham Forest and East London Collaborative (WELC) integrated care pioneer programme using the Researcher-in-Residence model. Issue 11 (6th November 2015) - Eyre, Laura; George, Bethan; Marshall, Martin
Abstract : Introduction: The integration of health and social care in England is widely accepted as the answer to fragmentation, financial concerns and system inefficiencies, in the context of growing and ageing populations with increasingly complex needs. Despite an expanding body of literature, there is little evidence yet to suggest that integrated care can achieve the benefits that its advocates claim for it. Researchers have often adopted rationalist and technocratic approaches to evaluation, treating integration as an intervention rather than a process. Results have usually been of limited use to practitioners responsible for health and social care integration. There is, therefore, a need to broaden the evidence base, exploring not only what works but also how integrated care can most successfully be implemented and delivered. For this reason, we are carrying out a formative evaluation of the Waltham Forest and East London Collaborative (WELC) integrated care pioneer programme. Our expectation is that this will add value to the literature by focusing on the processes by which the vision and objectives of integrated care are translated through phases of development, implementation and delivery from a central to a local perspective, and from a strategic to an operational perspective. Methods and analysis: The qualitative and process-oriented evaluation uses an innovative participative approach—the Researcher-in-Residence model. The evaluation is underpinned by a critical ontology, an interpretive epistemology and a critical discourse analysis methodology. Data will be generated using interviews, observations and documentary gathering. Ethics and dissemination: Emerging findings will be interpreted and disseminated collaboratively with stakeholders, to enable the research to influence and optimise the effective implementation of integrated care across WELC. Presentations and publications will ensure that learning is shared as widely as possible. The study has received ethical approval from University College London's Research Ethics Committee and has all appropriate NHS governance clearances.